Potential mechanism of ginger (Zingiber Officinale Roscoe) in alleviating osteoporosis - Luo, Miao; Li, Ning; Deng, Li; Pei, Huan; Wang, Funeng; Ma, Cong; Yang, Pengyi; Yuan, Kai; Li, Lvyu; Qin, Dongdong (Frontiers in Pharmacology, 2025)
Osteoporosis (OP), a prevalent metabolic bone disease, significantly compromises patients’ quality of life and overall health. In recent years, with the advancement of natural product research, ginger (Zingiber Officinale Roscoe) has garnered attention for its potential anti-osteoporotic effects. This review summarizes the clinical and basic research progress of ginger in alleviating OP, focusing on the mechanisms by which ginger exerts its effects through multiple signaling pathways, including NF-κB, Wnt/β-catenin, MAPK, GSK3β/Nrf2, and RANK/RANKL/OPG. By comprehensively analyzing existing literature, this study explores the research significance and limitations of ginger and its active metabolites in the treatment of OP, and proposes future research directions, aiming to provide theoretical support and reference for the development of novel anti-osteoporotic drugs.